2022
DOI: 10.1002/pchj.522
|View full text |Cite
|
Sign up to set email alerts
|

Composing in the scanner: A functional magnetic resonance imaging single case study on visual and auditory imagery

Abstract: Seeing with the mind's eye" and "hearing with the mind's ear" are two common indicators of musical imagery, and they can be referred to as "visual" and "auditory" musical imagery. However, a question remains open, that is, whether visual and auditory imagery of the same musical composition share the same neural mechanisms. Moreover, how can neural mechanisms guarantee the temporal flow of "musical imagery"? To answer these questions, we report here a preliminary single case study using functional magnetic reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Researchers employed temporal explicit tasks to demonstrate the substantial advantages of musicians over nonmusicians. Grondin et al and Izadifar et al, respectively, employed Weber functions 15 and functional magnetic resonance imaging 16 to validate the superiority of musicians over nonmusicians in temporal information processing. Rammsayer et al 17,18 demonstrated the superior ability of musicians over nonmusicians in processing temporal information across auditory and visual tasks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers employed temporal explicit tasks to demonstrate the substantial advantages of musicians over nonmusicians. Grondin et al and Izadifar et al, respectively, employed Weber functions 15 and functional magnetic resonance imaging 16 to validate the superiority of musicians over nonmusicians in temporal information processing. Rammsayer et al 17,18 demonstrated the superior ability of musicians over nonmusicians in processing temporal information across auditory and visual tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Grondin et al. and Izadifar et al., respectively, employed Weber functions 15 and functional magnetic resonance imaging 16 to validate the superiority of musicians over nonmusicians in temporal information processing. Rammsayer et al 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…There is also an interesting angle and unchartered territory to explore in mental imagery and time, referred to as subjective time perception in imagery. The brain appears to have a second clock that operates without sensory stimulation from the outside world (Isham & Izadifar, 2023; Izadifar et al, 2022). A wide variety of cognitive experiences involve mental imagery, namely the generation and manipulation of mental images without sensory input.…”
Section: Introductionmentioning
confidence: 99%